Case Report: Lifestyle changes and probiotic supplementation for improving longstanding type 2 diabetes in a male undergoing testosterone replacement therapy - Griffith, Anna; Perlman, Adam; Karr, Tara; Thompson, Marin Elise; Kolterman, Orville (Frontiers in Endocrinology, 2026)
A 52-year-old Caucasian male sought treatment for age-related testosterone decline. Past medical history included diagnosed hypertension and type 2 diabetes mellitus, with suboptimal glycemic control and no current antidiabetic therapy. He qualified for testosterone replacement therapy and agreed to address his metabolic dysfunction through enhanced lifestyle interventions and a targeted 5-strain probiotic as well as other supplements. At 3 months, the patient demonstrated improved glycemic control (hemoglobin A1c decreased from 7.2% to 5.9%) and improvement in newly documented mixed hyperlipidemia. At 6 months, testosterone levels normalized with replacement therapy, and the patient achieved modest weight reduction with favorable body composition changes: 13.2-lb decrease in fat mass, as well as a 6.1% reduction in body fat percentage and a 5.1-lb increase in skeletal muscle mass. This case demonstrates the feasibility and clinical efficacy of combining lifestyle interventions with targeted supplementation in a patient with metabolic syndrome who preferred non-pharmacological management strategies.